Matilda effect: challenges to the visibility and recognition of women in Health Sciences - Rodríguez, Daliannis (Revista Gregoriana de Ciencias de la Salud, 2025)
This letter to the editor addresses the persistent Matilda Effect, which invisibilizes or downplays women’s scientific contributions, particularly in the Health Sciences. Despite increasing female participation in academia and research, structural barriers still limit their access to funding, leadership, authorship, and recognition. The author illustrates this bias through historical and contemporary examples, from Rosalind Franklin and Alice Ball to Katalin Karikó. In Ecuador, marked disparities persist in STEM fields, as well as discrimination and harassment in surgical specialties. The letter proposes that scientific journals adopt equitable editorial policies—such as gender-balanced boards, blind peer review, and gender indicator monitoring—to foster ethical and inclusive science. The author calls on the academic community to reflect on and challenge the practices that perpetuate this inequity, in order to build a more diverse and just scientific ecosystem.